The Multisided Threat to Free Trade: Protectionism and Fair Trade During Increasing Populism - Ehrlich, Sean D. (2023)
The standard embedded liberalism argument for increasing free trade after World War II is that countries have compensated those hurt by trade and, therefore, have reduced opposition to free trade policies. This argument relies on opposition to trade being motivated by personal economic effects of trade; however, recent work has increasingly found other motivations for protectionism, calling into question the sustainability of embedded liberalism. This article argues that this threat to embedded liberalism will grow worse as populism increases, which leads to both more nationalistic and more economic opposition to trade, which is only partially offset by other non-economic opposition (most notably, fair trade) decreasing. This article offers a conceptual framework for the different types of opposition to trade and how increasing populism influences its composition. The framework is supported by descriptive statistics of public opinion on trade policy in the US over the past two decades, encompassing trade opinions before and during the global financial crisis, as well as during the rise of global populist movements starting around 2016. We conclude the article with policy implications regarding the multi-sided threat to free trade and how policymakers can confront the evolving challenges to embedded liberalism.